Professionals’ Perspectives of Smart Stationary Bikes in Rehabilitation: Qualitative Study - Julie Soulard; Dahlia Kairy; Roua Walha; Cyril Duclos; Sylvie Nadeau; Claudine Auger (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundStationary bikes are used in numerous rehabilitation settings, with most offering limited functionalities and types of training. Smart technologies, such as artificial intelligence and robotics, bring new possibilities to achieve rehabilitation goals. However, it is important that these technologies meet the needs of users in order to improve their adoption in current practice. ObjectiveThis study aimed to collect professionals’ perspectives on the use of smart stationary bikes in rehabilitation. MethodsTwelve health professionals (age: mean 43.4, SD 10.1 years) completed an online questionnaire and participated in a semistructured interview regarding their needs and expectations before and after a 30-minute session with a smart bike prototype. ResultsA content analysis was performed with inductive coding. Seven main themes emerged: (1) bike functionalities (cycling assistance, asymmetric resistance, and forward and backward cycling), (2) interface between bike and users (simple, user-friendly, personalized, with written reminders during training), (3) feedback to users (user and performance data), (4) training programs (preprogrammed and personalized, and algorithmic programs), (5) user engagement (telerehabilitation, group sessions, music, and automatic suggestion of training), (6) the bike as a physical device (dimensions, comfort, setup, screen, etc), and (7) business model (various pricing strategies, training for professionals, and after-sales service). ConclusionsThis study provides an interpretive understanding of professionals’ perspectives regarding smart stationary bikes and is the first to identify the expectations of health professionals regarding the development of future bikes in rehabilitation.